2017
DOI: 10.1093/pubmed/fdx177
|View full text |Cite
|
Sign up to set email alerts
|

The impact of Adverse Childhood Experiences on social determinants among Saudi adults

Abstract: ACEs are highly prevalent in SA and have significant negative impact on life opportunities. National preventive programs should be implemented to reduce ACE and their deleterious outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 29 publications
1
21
2
Order By: Relevance
“…For women, there is no evidence about the relationship between exposure to collective violence and tobacco use. However, the Saudi ELA study showed that exposure to four or more ELAs increased the risk for tobacco use for females more than for males (Almuneef, ElChoueiry, Saleheen, & Al‐Eissa, ).…”
Section: Discussionmentioning
confidence: 99%
“…For women, there is no evidence about the relationship between exposure to collective violence and tobacco use. However, the Saudi ELA study showed that exposure to four or more ELAs increased the risk for tobacco use for females more than for males (Almuneef, ElChoueiry, Saleheen, & Al‐Eissa, ).…”
Section: Discussionmentioning
confidence: 99%
“…There were four studies in the USA [47][48][49][50], three in the UK [51][52][53], two in Hong Kong [54][55] two in Taiwan [56][57], and two in Germany [58,59]. There was one study in Denmark [60], the Netherlands [61], Switzerland [62], Japan [63], Suriname [64], Saudi Arabia [65], Israel [66], South Africa [67], and Hungary [68]. In the Balkans study [46], eight met eligibility criteria based on the number of types of maltreatment studied: Albania, Bosnia & Herzegovina, Bulgaria, Croatia, the Former Yugoslavian Republic of Macedonia, Greece, Romania, and Serbia; in general for our purposes, we treat these as one study.…”
Section: Systematic Reviewmentioning
confidence: 99%
“…Fourteen studies measured all five maltreatment types [47][48][49][50][51]53,[56][57]61,[64][65][66][67][68]. Of nine studies measuring four maltreatment types, seven omitted EDV [46,52,[58][59][60][62][63], and two omitted sexual abuse [54][55].…”
Section: Systematic Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…This has enabled studies comparing ACE footprints, with the particular profile of countries differing, mainly due to the combination effects of socio economic conditions and cultural traditions (Bellis et al, 2014). For example, whilst ACE studies in western industrialised countries indicate that around 15% of the population have an ACE score of four or more (a level, which is rather arbitrarily regarded as clinical), Saudi Arabia has 29% of its population at this level (Almuneef et al, 2017). How ACE national profile scores are comprised also features significant variation, with for example, much higher numbers of citizens in the US receiving prison sentences than is the case in European countries (Bellis et al, 2014).…”
Section: The Development Of Ace Researchmentioning
confidence: 99%